Sensory characterization of unpeeled robusta coffee at different roasting temperature and time - Kiki Fibrianto; Harijono Harijono; Syaiful Adnan (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2022)
Unpeeled coffee is a traditional post-harvest coffee production method with minimum waste. However, its sensory quality is relatively inferior compared to the peeled coffee beans. The sensory characteristics of unpeeled coffee can be optimized after the natural drying process by determining the roasting temperature and brewing technique to improve sensory preferences on several attributes tested, such as sweetness, bitterness, sourness, and grassy flavor as roasting and brewing are two major processes for developing coffee flavors. The beans were pre-treated by natural sun-drying as well as oven drying. A Central Composite Design on Response Surface Methodology was used to optimize the roasting temperature within the range of 179oC and 221oC and the roasting time within the range of 10 to 20 minutes for the optimum bean’s moisture content (%). The best-unpeeled coffee beans were obtained after three weeks of natural drying (approximately 28oC on average) and roasted at 221oC for 16 minutes. At this stage, the preferences for French-press brewed coffee were the highest, especially for the sweetness attribute. This might be supported by the fact that 2-methyl-5-hexen nitrile and 3-methyl-4-penten-1-ol were identified on GC-MS as the dominant detected volatile compounds.